Pengaruh Integritas dan Komunikasi terhadap Kinerja Karyawan di PT Parkland World Indonesia - Widowati Widowati; Lia Wati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is a critical factor in achieving organizational goals, and it is influenced by various personal and organizational factors, including integrity and communication. In a competitive business environment, companies must ensure that employees not only possess technical competence but also demonstrate ethical behavior and effective communication skills to enhance productivity and organizational effectiveness. This study aims to examine the effect of integrity and communication on employee performance at PT Parkland World Indonesia. A quantitative survey method was employed, with the entire population of 70 employees serving as the sample using a saturated sampling technique. Data were collected through a Likert-scale questionnaire (1–5) and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 25. The findings reveal that both integrity and communication simultaneously have a significant positive effect on employee performance. The coefficient of determination indicates that 69.4% of the variation in employee performance is explained by integrity and communication, while the remaining 30.6% is influenced by other factors not included in this study. These results highlight the importance of fostering ethical behavior and effective communication in enhancing employee performance and suggest that management should implement integrated training and development programs to strengthen these key competencies.